Hexavalent chromium adsorption on impregnated palm shell activated carbon with polyethyleneimine - Owlad, M.; Aroua, Mohamed Kheireddine; Daud, Wan Mohd Ashri Wan (Elsevier, 2010)
Removal of Cr(VI) ions from aqueous solution was investigated using modified palm shell activated carbon. Low Molecular Weight Polyethyleneimine (LMW PEI) was used for impregnation purpose. The maximum amount of LMW PEI adsorbed on activated carbon was determined to be approximately 228.2 mg/g carbon. The adsorption experiments were carried out in a batch system using potassium dichromate K2Cr2O7 as the source of Cr(VI) in the synthetic waste water and modified palm shell activated carbon as the adsorbent. The effects of pH, concentration of Cr(VI) and PEI loaded on activated carbon were studied. The adsorption data were found to fit well with the Freundlich isotherm model. This modified Palm shell activated carbon showed high adsorption capacity for chromium ions.